2018
DOI: 10.18203/2349-2902.isj20184083
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of traumatic Extradural Hematoma (EDH) using Glasgow Outcome Scale (GOS)

Abstract: Background: Outcome in patient with EDH depends on various factors like GCS at presentation, Volume of hematoma, time of intervention, age, location of hematoma, etc. This study was carried out to find out correlation (if any) between outcome and various factors affecting it. Aim and objectives of this study were to study outcome of patients with traumatic EDH in terms of poor outcome (GOS score 1,2,3), Good outcome (GOS Score 4,5)Methods: This study was carried out in 91 patients having positive CT Head for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Male patients predominated in the study, a trend consistent with wider demographic patterns in head injury incidents, likely due to increased male exposure to accidents and conflicts. The mean age of participants in this study was 27.04 ± 7.74 years, aligning with the findings of Prajapati et al, who also reported a similar mean age, highlighting the vulnerability of this age group to head injuries (1). The crucial role of prompt detection and surgical decompression of hematomas in improving patient outcomes was evident.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Male patients predominated in the study, a trend consistent with wider demographic patterns in head injury incidents, likely due to increased male exposure to accidents and conflicts. The mean age of participants in this study was 27.04 ± 7.74 years, aligning with the findings of Prajapati et al, who also reported a similar mean age, highlighting the vulnerability of this age group to head injuries (1). The crucial role of prompt detection and surgical decompression of hematomas in improving patient outcomes was evident.…”
Section: Discussionsupporting
confidence: 90%
“…Head injuries are a significant concern in emergency departments, representing about 3.4% of all visits, with an annual incidence rate of approximately 450 cases per 100,000 people (1). These injuries often lead to traumatic brain injury (TBI), with an incidence rate of 20-40 per 100,000 individuals annually (2).…”
Section: Introductionmentioning
confidence: 99%
“…Also, for initial hematoma volume more than 30ml; among 59 patients, 53(89.8%) patients recovered with favourable outcome. Outcome is much better than of adult patients 27,28 .…”
Section: Resultsmentioning
confidence: 90%
“…EDH still remains a serious neurological condition (8,9,10). Extradural hematomas (EDH) accounts for 2.7-4% of traumatic brain injuries (TBI) and majority of the reported cases are in second or third decade of their life (11,12). Extradural hematoma (EDH) life threatening lesion in neurological surgery was killing at least four of five patients previously but in the modern era of computed brain imaging which is affording prompt, precise diagnosis in the trauma patients, EDH has become one of the disease conditions that may truly be called the delight of a neurosurgeon.…”
Section: Extradural Hematoma In Pakistanmentioning
confidence: 99%